The nerve-tumour regulatory axis GDNF-GFRA1 promotes tumour dormancy, imatinib resistance and local recurrence of gastrointestinal stromal tumours by achieving autophagic flux. (1st June 2022) - Ni, Bo; Li, Qing; Zhuang, Chun; Huang, Peiqi; Xia, Xiang; Yang, Linxi; Ma, Xinli; Huang, Chen; Zhao, Wenyi; Tu, Lin; Shen, Yanying; Zhu, Chunchao; et al.
Abstract: Complete surgical resection, accessible therapeutic targets and effective tyrosine kinase inhibitors (TKIs) have not completely cured gastrointestinal stromal tumours (GISTs), with most patients suffering from residual tumours and recurrence. The existence of nerve infiltration in GIST provides a way for tumour cells to escape local resection and systemic targeted therapy, which may challenge the previous understanding of its behaviour patterns and inspire the development of more radical excision and more precise targeted therapy. Moreover, tumour dormancy has emerged as a major cause of drug resistance and tumour relapse. Among these pathways, the nerve-tumour regulatory axis GDNF-GFRA1 is activated in GISTs, assists tumour cells in achieving dormancy and protects them from apoptosis under environmental stress by enhancing autophagic flux. The concrete mechanism is that the GDNF-regulating interaction between GFRA1 and the lysosomal calcium channel MCOLN1 activates Ca 2+ -dependent TFEB signalling. Activated TFEB transcriptionally regulates intracellular lysosome levels, which could achieve feedback upregulation of cellular autophagy flux during TKI treatment. This dormancy-transition axis fills parts of the mechanistic vacancy before the onset of secondary mutations, and strategies for TKIs combined with targeting GFRA1-dependent autophagy have distinct promise as prospective clinical therapies. Highlights: The symbiosis of infiltrating nerves and GIST cells correlates with drug resistance and tumour recurrence. GDNF derived from nerves could promote dormant-state transition and therapeutic resistance of GIST cells through GFRA1. The underlying mechanism of dormancy is the activated autophagy achieved by GFRA1-dependent MCOLN1/Ca2+/TFEB pathway. This dormant-state transition supposes an integrated treatment of GIST, combining TKIs with anti-autophagy therapy.